Genomic insights into antimicrobial resistance and virulence of E. coli in central Ethiopia: a one health approach - Chekole, Wagaw Sendeku; Potgieter, Lizel; Adamu, Haileeyesus; Sternberg-Lewerin, Susanna; Tessema, Tesfaye Sisay; Magnusson, Ulf (Frontiers in Microbiology, 2025)
Antimicrobial resistance is a global threat causing millions of deaths annually. The study aimed to identify antibiotic resistance genes (ARGs), mobile genetic elements (MGEs), and virulence genes (VGs) and track their dissemination among E. coli isolates. Seventy-seven isolates from calves, environments, and human sources were studied. The study involved WGS sequencing, bacterial strains characterized; pan genome, multi-locus sequence typing, and serotyping using O-, and H-typing. The ARGs, VGs, and MGEs were identified using ABRicate against selected respective databases. A maximum likelihood SNP (single nucleotide polymorphism) tree was constructed and visualized with an interactive tree of life (IToL). Descriptive statistics were used to analyze the data. Seventy-seven of the isolates were identified as E. coli, later grouped into 5 clades and four known phylogroups. ST10 and O16:H48 were most prevalent in 12 and 42 isolates, respectively. There were about 106 unique ARGs detected between 1.3% and 91.9%, with 57 detected in 40% of isolates. In terms of ARGs, the most common were bla-ampH (90.9%), bla-AmpC1 (89.6%), tet(A) (84.4%), mdf(A) (81.8%), aph(3“)-Ib (79%), sul2 (79%), aph(6)-Id (75%), and bla-PBP (70%). It was found that 95 percent (96/106) of ARGs came from at least two sources. The majority of detected ARGs exhibited high concordance between phenotypic resistance and ARGs profiles (JSI ≥ 0.5). In eight isolates, mutations in the gyrA (3) and par-C/E (5) genes led to ciprofloxacin and nalidixic acid resistance. The most common co-occurrences of ARG and MGE were Tn3 with bla-TEM-105 (34), Int1 with sul1 (13), and dhfr7 (11). Meanwhile, the most frequently detected VGs (n ≥ 71 isolates) included elfA-G, fimB-I, hcpA-C, espL, ibeC, entA, fepA-C, ompA, ecpA-E, fepD, fes, and ibeB. Nearly, 88.3% (128/1450) VGs were shared in isolates from at least two sources. ETEC (53.2%), EAEC (22.1%), and STEC (14.3%) were the three most frequently predicted pathotypes. Despite significant ST diversity, ARGs and VGs showed an extensive distribution among the study groups. These findings suggest limited clonal transmission of isolates. In comparison, the wide distribution of ARGs and VGs may be attributed to horizontal gene transfer driven by similar antibiotic selection pressures in the study area.